10.1016/s1558-0164(10)70339-4 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Prostate cancer (PCa) and benign prostatic hyperplasia (BPH) significantly affect men's quality of life. Due to low PSA specificity, more sensitive genetic and protein markers are needed. This study comparatively evaluates variations in NOTCH1 and NOTCH3 gene regions-key components of the Notch pathway-and serum protein levels in PCa and BPH patients. METHODS: The study included 90 individuals: 15 healthy controls, 25 BPH, 25 localized PCa (LPCa), and 25 metastatic PCa (MPCa) patients. NOTCH1 and NOTCH3 gene regions were analyzed via Sanger sequencing, and serum protein levels were measured using ELISA. RESULTS: Genetic analyses revealed that the novel NOTCH1 g.54305 T>A variation (p = 0.0001), rs2133314984 (p = 0.015), and rs577451694 (p = 0.0012) variants were significantly associated with increased PCa risk. Additionally, the NOTCH3 rs746192089 variation was linked to disease risk (p = 0.0005), whereas the rs1044009 variant showed no statistically significant difference. Protein assessments showed that serum NOTCH1 concentrations were significantly lower in LPCa (p = 0.006) and MPCa (p = 0.003) groups than controls. Serum NOTCH3 levels were significantly decreased (p ≤ 0.002) in BPH, LPCa, and MPCa groups, with the lowest levels in the metastatic stage. Wild-type NOTCH1 g.54305 TT and NOTCH3 rs746192089 CC genotypes were associated with significantly higher serum protein expression than mutant-allele genotypes (p = 0.036 and p < 0.001, respectively). CONCLUSIONS: In conclusion, specific NOTCH1 and NOTCH3 variations are linked to disease risk, and decreased serum protein levels correlate with advanced clinical stages, providing insights into the Notch pathway's role in PCa pathogenesis.